Peran Analisis Big Data Dalam Sektor Industri Di Indonesia - Cindy Destyana Putri; Terttiaavini Terttiaavini; Ajeng Oktatriani (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2023)
Abstrak - Seiring perkembangan teknologi saat ini yang sangat pesat memberikan kemudahan untuk berbagai sektor yang ada didunia, tidak terkecuali pada sektor industri. Pada dasarnya penggunaan teknologi memang memberikan banyak manfaat dan dampak yang positif bagi perusahaan-perusahaan baik perusahaan besar maupun berkembang/startup seperti memudahkan dalam kegiatan pemasaran, pemesananan, dan pengiriman produk dan jasa. Saat ini kita akan memasuki era yang disebut dengan Revolusi Industri 5.0 yang mana fungsi tenaga manusia akan hampir sama dengan kecanggihan teknologi. Maka dari itu analisis Big Data akan sangat berpengaruh bagi para usahawan dalam mengembangkan produk dan jasa mereka. Dengan menggunakan teknologi canggih perusahaan dapat meningkatkan kualitas produk dan jasa yang mereka tawarkan sehingga akan mendapatkan feedback yang baik dari konsumen dan memperkuat posisi mereka di pasar.Kata kunci: Big Data, 5.0 Industrial Revolution Abstract - Along with the current rapid development of technology, it provides convenience for various sectors in the world, including the industrial sector. The use of technology does provide so many positive benefits and impacts for companies, both large and startup, such as facilitating marketing, ordering dan delivery of products and services. We are currently entering an era called the 5.0 Industrial Revolution, in which the function of human power will be almost the same as technological sophistication. Therefore, Big Data analysis will be very influential for entrepreneurs in developing their products and services. By using advanced technology, companies can improve the quality of their products and services Along with the current rapid development of technology, it provides convenience for various sectors in the world, including the industrial sector. The use of technology does provide many positive benefits and impacts for companies, both large and developing companies/startups, such as facilitating marketing, ordering, and delivery of products and services. We are currently entering an era called the 5.0 Industrial Revolution, in which the function of human power will be almost the same as technological sophistication. Therefore Big Data analysis will be very influential for entrepreneurs in developing their products and services. By using advanced technology, companies can improve the quality of the products and services they offer so that they will get good feedback from consumers and strengthen their position in the market.Keywords: Big Data, 5.0 Industrial Revolution